Arm's-length transactions as a source of incomplete cross-border transmission: The case of autos - Rebecca Hellerstein; Sofia Berto Villas-Boas (Federal Reserve Bank of New York, 2006)
A large share of international trade occurs through intrafirm transactions. We show that this common cross-border organization of the firm has implications for the welldocumented incomplete transmission of shocks across such borders. We present new evidence of an inverse relationship between a firm's outsourcing of inputs and its rate of exchange rate pass-through. We then develop a structural econometric model with final assemblers and upstream parts suppliers to quantify how firms' organization of their activities across national borders affects their pass-through behavior.
Keywords: F14; F3; F4; 330; exchange rate pass-through; intrafirm trade; outsourcing; vertical contracts; Firmeninterner Handel; Multinationales Unternehmen; Exchange Rate Pass-Through; Verrechnungspreis; Kraftfahrzeugmarkt; USA